BEHAVIOR OF WEAR-RESISTANT EPOXY COMPOSITIONS IN CONDITIONS OF CONTACT-DYNAMIC LOADING - Полоз, Олексій Юрійович; Ебіч, Юрій Рахмієлевич (Problems of Friction and Wear, 2021)
A significant amount of industrial equipment in Ukraine and the world operates under conditions of severe shock-abrasive wear under dynamic loading, to protect the restoration of which epoxy composite materials are used using high-hard Mohs fillers - silicon and boron carbides, silicon nitride, corundum, etc. Analysis of the terms of operation and causes of destruction of parts and equipment in contact with abrasive streams, showed that the problem of improving its reliability remains relevant for the mining, gas industry, a number of other industries. This problem is solved by the introduction of new wear-resistant materials, and further expansion of the range of wear-resistant parts and increase their service life is associated with the need to develop knowledge in the field of wear of epoxy compositions. However, studies, which consider the wear of epoxy compositions in the flow of abrasive materials, practically do not consider such important aspects of the problem as the stages of deformation and their relationship with characteristics of materials. The influence of the deformation energy components - elastic and viscous on the course of active (introduction in the matrix) and passive (rebound) phases of the process is determined and rectilinear dependences between these parameters for unfilled epoxy compositions are established; for silicon-filled carbide composites, the nature of these dependences changes to nonlinear, which is due to the contribution to the process of deformation of the formed dispersed structure. The dependence of intensive gas abrasive wear silicon carbide F1000 filled epoxy composites on the ratio of energies of elastic and viscous deformation is established and it is shown that at characteristic for industrial compositions elevated concentrations of filler (> 200 wt.h. per 100 wt.h. epoxy resin) has an impact on the process of deformation of the structural parameter A of the polymer-filler interaction and the density of the polymer layer at the phase boundary ρn. It was found that the wear resistance of industrial epoxy composites is consistent with the main parameters of the process of their deformation under contact-dynamic loading.